Communicative Approach in Managerial Supervision from an Islamic Educational Perspective: Improving School Evaluation at SDN 14 Selayo, Solok Regency - Yusnimaranti Yusnimaranti; Jamilus Jamilus (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to describe the implementation of a communicative approach in managerial supervision as an effort to improve the quality of school evaluation at SDN 14 Selayo, Solok Regency. Effective managerial supervision requires open, dialogic communication based on trust between the principal and teachers. This research uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and education staff at SDN 14 Selayo. The findings show that the implementation of a communicative approach in managerial supervision significantly improves the quality of school evaluation, including program planning, instructional implementation, and reporting of evaluation results. This approach is able to build a conducive school climate, increase teacher motivation, and foster a reflective culture within the school environment. It is concluded that managerial supervision with a communicative approach is an appropriate and effective strategy to enhance the overall quality of school evaluation.